2021
DOI: 10.5334/ijic.5540
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Implementation of Flexible Assertive Community Treatment – an Integrated Community-based Treatment Model for Patients with Severe Mental Illness

Abstract: Introduction: Flexible Assertive Community Treatment (FACT) is a model of integrated care aiming to increase continuity of care for individuals with severe mental illness. FACT teams have been implemented in many countries by merging Assertive Community Treatment (ACT) and standard care from Community Mental Health teams (CMHTs). However, there has been little research on how practitioners experienced the fusion of these teams. Aim: This study explores how former ACT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 30 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…This can be a useful modi cation wherein one adds an element to the model. Studies have shown that ACT [14] and FACT [13] teams can mitigate the problem of long travel distances using digital meetings, including in situations of crisis management [14]. Both the present study and another Norwegian study [68] described how virtual communication increased in the FACT teams because of the COVID-19 pandemic.…”
Section: Innovative Modi Cations Can Increase the Potential Of The Fa...mentioning
confidence: 53%
See 4 more Smart Citations
“…This can be a useful modi cation wherein one adds an element to the model. Studies have shown that ACT [14] and FACT [13] teams can mitigate the problem of long travel distances using digital meetings, including in situations of crisis management [14]. Both the present study and another Norwegian study [68] described how virtual communication increased in the FACT teams because of the COVID-19 pandemic.…”
Section: Innovative Modi Cations Can Increase the Potential Of The Fa...mentioning
confidence: 53%
“…The long travel distances to patients and facilities made the accomplishment of these elements particularly di cult. Studies of ACT teams [39,40] and a Danish study of FACT teams [13] also found that travel distances can affect the intensity of outreach care. Di cult driving conditions can further complicate this issue.…”
Section: The Rural Context Challenges the Potential Of The Fact Modelmentioning
confidence: 98%
See 3 more Smart Citations